Pengaruh Kualitas Layanan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan pada Aplikasi Gopay - Ferdy Ilham Muhammad Zam Zam; Ratih Hendayani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In the era of digitalization, Indonesians' internet consumption patterns increasingly drive the use of digital wallets for electronic payments. The popularity of digital wallets triggers competition in Indonesia's financial technology industry, encouraging companies to maintain customer loyalty to avoid brand-switching. This research provides insights into how service quality contributes to customer satisfaction and loyalty, addressing the research gap regarding digital wallets and inconsistencies in previous studies on service quality and customer loyalty. The objective is to identify whether the decline in customer satisfaction and service quality in the Gopay digital wallet application causes declining customer loyalty. This research uses quantitative methods with descriptive and causal aims. The research population is Indonesian Gopay users, with non-probability sampling of 385 respondents. Structural Equation Modeling (SEM) was used for data analysis with AMOS 24 software. Research findings show that user satisfaction with the Gopay application is significantly and positively influenced by service quality. In addition, contributing to overcoming the gap between previous research findings and service quality results has a significant and positive effect on customer loyalty to the Gopay application. Customer satisfaction is significant and positive on Gopay application loyalty. In addition, the service quality and customer loyalty of the Gopay application are positively influenced by the meaningful and constructive mediation function played by customer satisfaction. By selecting specific regions for a more thorough assessment of the financial results related to the Gopay application, future researchers may be able to use this research as a reference and point of reference.